Culture and inflation in Weimar Germany - Widdig, Bernd (University of California Press, 2001)
For many Germans the hyperinflation of 1914-1923 was one of the most decisive experiences of the 20th century. This study investigates the effects of that inflation on German culture during the Weimar Republic.
Keywords: Germany -- Social conditions -- 1918-1933.; Inflation (Finance) -- Germany -- History.; Germany -- History -- 1918-1933.; Germany -- Economic policy -- 1918-1933.; German literature -- 20th century -- History and criticism.; Germany -- Civilization -- 20th century.; Money in literature.; Antisemitism -- Germany -- History -- 20th century.; Allemagne -- Conditions sociales -- 1918-1933.; Inflation -- Allemagne -- Histoire.; Allemagne -- Histoire -- 1918-1933.; Allemagne -- Politique économique -- 1918-1933.; Littérature allemande -- 20e siècle -- Histoire et critique.; Allemagne -- Civilisation -- 20e siècle.; Antisémitisme -- Allemagne -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Inflation.; Antisemitism; Civilization; Economic policy; German literature; Inflation (Finance); Money in literature; Social conditions; Germany; Geschichte; Inflation; Kultur; Kunst; Deutschland; Weimarer Republik; Wirtschaft; 1900-1999; Criticism, interpretation, etc.; History